Process for producing depolymerized cellulose ethers
By controlling the contact temperature of the aqueous solution of cellulose ether and acid, the problem of the formation of crude aggregates and black pollutants when understanding polycellulose ether is solved, the quality of cellulose ether is improved and the generation of yellowness is inhibited.
Patent Information
- Application Number
- CN202111230383.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-22
- Filing Date
- 2021-10-21
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2041-10-21
AI Technical Summary
When disposal of cellulose ether with aqueous hydrogen chloride solution, crude aggregates and black contaminants may be generated, resulting in deterioration of the quality of cellulose ether.
By controlling the temperature at which the cellulose ether and the aqueous solution of acid contact each other, the temperature of the cellulose ether is specifically controlled from 45°C to 95°C and the aqueous solution of acid is controlled from 55°C to 98°C to inhibit the formation of crude aggregates and reduce the formation of black pollutants.
The generation of crude aggregates and black pollutants is inhibited when depolymerizing cellulose ether, the quality of cellulose ether is improved, and the generation of yellowness is inhibited.
Smart Images

Figure BDA0003314886370000111
Abstract
Description
Technical Field
[0001] The present invention relates to a process for producing depolymerized cellulose ether, wherein the depolymerized cellulose ether is obtained by depolymerizing cellulose ether. Background Art
[0002] For example, cellulose ethers with a low degree of polymerization are used as film coatings for solid preparations such as tablets. Such film coatings are used to mask the unpleasant taste of drugs and to prevent drug deterioration or control elution behavior in the digestive organs after administration.
[0003] Typically, cellulose ethers with a low degree of polymerization are obtained by depolymerizing cellulose ethers with a high degree of polymerization. Depolymerization with an acid such as hydrogen chloride is widely used. It is also known that the cellulose ethers obtained with a low degree of polymerization have a higher yellowness than the starting cellulose ethers with a high degree of polymerization.
[0004] In order to suppress yellowness, there is provided a method for producing cellulose ether having a low degree of polymerization, the method comprising the steps of: contacting a powdery water-soluble cellulose ether having a high degree of polymerization with an aqueous solution of hydrogen chloride, wherein the amount of hydrogen chloride is 0.1 to 1% by weight relative to the weight of the cellulose ether, and the water content of the reaction system is 3 to 8% by weight; placing the resulting mixture in a reactor, reacting at 40° C. to 85° C.; and then removing the hydrogen chloride (JPS62-025101A). Since neither the internal temperature of the reactor nor heating is described, the contact and mixing between the cellulose ether and the aqueous solution of hydrogen chloride for reaction are assumed to be performed at room temperature. Summary of the invention
[0005] However, in the method using aqueous hydrogen chloride solution, wherein the amount of hydrogen chloride is 0.1 wt % to 1 wt % and the water content of the reaction system is 3 wt % to 8 wt %, the yellowness of the obtained cellulose ether with a low degree of polymerization is suppressed, but when the aqueous hydrogen chloride solution is added, coarse aggregates may be generated. Even after depolymerization, the coarse aggregates may remain as aggregates, so the quality of the produced cellulose ether with a low degree of polymerization deteriorates. Alternatively, the coarse aggregates may be excessively depolymerized during the depolymerization reaction and become black, and then decomposed in the steps after the depolymerization reaction, so the quality of the cellulose ether with a low degree of polymerization may be deteriorated due to the presence of black pollutants. Therefore, there is room for improvement.
[0006] In view of the above circumstances, an object of the present invention is to provide a method for producing depolymerized cellulose ether, in which the formation of coarse aggregates is suppressed during contact with an aqueous acid solution, and the amounts of aggregates and black contaminants are reduced while suppressing yellowness.
[0007] As a result of extensive studies to achieve this object, the present inventors have found that, by controlling the temperature at which cellulose ether and an aqueous acid solution are brought into contact with each other, depolymerized cellulose ether can be produced while suppressing the formation of coarse aggregates during the contact of cellulose ether with an aqueous acid solution, reducing the amounts of aggregates and black contaminants, and suppressing yellowness; thereby completing the present invention.
[0008] In one aspect of the present invention, there is provided a method for producing depolymerized cellulose ether, comprising a depolymerization step of depolymerizing the cellulose ether, namely, obtaining the depolymerized cellulose ether by contacting the cellulose ether at 45 to 95° C. with an aqueous acid solution at 55 to 98° C.
[0009] It should be noted that the depolymerized cellulose ether has a lower degree of polymerization than the pre-depolymerized cellulose ether, and may include cellulose ethers having a low degree of polymerization for use in, for example, film coating of solid preparations (eg, tablets).
[0010] According to the present invention, depolymerized cellulose ether can be produced while suppressing the formation of coarse aggregates during contact with an aqueous acid solution, reducing the amounts of aggregates and black contaminants, and suppressing yellowness. DETAILED DESCRIPTION
[0011] The depolymerized cellulose ether is obtained by depolymerizing the cellulose ether by contacting the cellulose ether at 45° C. to 95° C. with an aqueous acid solution at 55° C. to 98° C.
[0012] The temperature of the pre-depolymerized cellulose ether to be depolymerized is 45 to 95° C., preferably 60 to 90° C., more preferably 63 to 87° C., and still more preferably 65 to 85° C. When the temperature is lower than 45° C., the generation amount of coarse aggregates and black contaminants increases. When the temperature exceeds 95° C., depolymerized cellulose ether with low yellowness cannot be obtained.
[0013] The method of heating the cellulose ether to be depolymerized is not particularly limited. Examples of the method of heating the cellulose ether include a method of placing the cellulose ether in a reactor equipped with a jacket and heating it with hot water or steam in the jacket; a method of heating the cellulose ether by allowing heated air, nitrogen, etc. to pass through the cellulose ether.
[0014] The temperature of the cellulose ether to be depolymerized can be controlled, for example, by controlling the jacket temperature of the reactor used to carry out the depolymerization.
[0015] Examples of cellulose ethers include hydroxyalkyl alkyl cellulose, alkyl cellulose, and hydroxyalkyl cellulose.
[0016] Examples of the hydroxyalkyl alkyl cellulose include hydroxypropyl methyl cellulose (hereinafter also referred to as “HPMC”) having a hydroxypropoxy group content of preferably 4.0% by mass to 13.0% by mass and a methoxy group content of preferably 19.0% by mass to 32.0% by mass; hydroxyethyl methyl cellulose having a hydroxyethoxy group content of preferably 4.0% by mass to 15.0% by mass and a methoxy group content of preferably 20.0% by mass to 26.0% by mass; and hydroxyethyl ethyl cellulose having a hydroxyethoxy group content of preferably 8.0% by mass to 20.0% by mass and an ethoxy group content of preferably 20.0% by mass to 38.0% by mass.
[0017] Examples of the alkylcellulose include methylcellulose (hereinafter also referred to as “MC”) having a methoxy group content of preferably 18.0% by mass to 36.0% by mass; and ethylcellulose having an ethoxy group content of preferably 40.0% by mass to 50.0% by mass.
[0018] Examples of the hydroxyalkyl cellulose include hydroxyethyl cellulose having a hydroxyethoxy group content of preferably 2.0% by mass to 70.0% by mass; and hydroxypropyl cellulose having a hydroxypropoxy group content of preferably 2.0% by mass to 70.0% by mass.
[0019] The contents of the alkoxy group and the hydroxyalkoxy group in the alkyl cellulose, hydroxyalkyl cellulose and hydroxyalkyl alkyl cellulose can be determined according to the measurement in "Hydroxypropylmethylcellulose" of the Japanese Pharmacopoeia (17th edition).
[0020] From the viewpoint of washability of the cellulose ether to be depolymerized, the viscosity of a 2 mass % aqueous solution of the cellulose ether to be depolymerized at 20° C. is preferably 400 to 200,000 mPa.s, more preferably 400 to 150,000 mPa.s, still more preferably 400 to 100,000 mPa.s.
[0021] When the viscosity of a 2 mass % aqueous solution of cellulose ether at 20° C. is 600 mPa·s or more, the viscosity may be determined by using a single cylinder type rotational viscometer in accordance with “Viscosity measurement by rotational viscometer” in the commonly used tests of the Japanese Pharmacopoeia (17th edition). When the viscosity of a 2 mass % aqueous solution of cellulose ether at 20° C. is less than 600 mPa·s, the viscosity may be determined by using an Ubbelohde viscometer in accordance with “Viscosity measurement by capillary viscometer” in the commonly used tests of the Japanese Pharmacopoeia (17th edition).
[0022] The cellulose ether to be depolymerized can be prepared by a known method. For example, it is produced by a method comprising the steps of contacting an alkali metal hydroxide solution with pulp to obtain alkali cellulose; reacting alkali cellulose with an etherifying agent to obtain crude cellulose ether; one or more steps of washing and drying the crude cellulose ether; and an optional pulverizing step of pulverizing the washed and dried cellulose ether.
[0023] The alkali metal hydroxide solution is not particularly limited. From an economic point of view, an alkali metal hydroxide aqueous solution is preferred. The alkali metal hydroxide aqueous solution is not particularly limited. From an economic point of view, a sodium hydroxide aqueous solution is preferred.
[0024] The etherifying agent is not particularly limited. Examples thereof include alkyl halides such as methyl chloride and ethyl chloride; and alkylene oxides such as ethylene oxide and propylene oxide.
[0025] The water content of the cellulose ether to be depolymerized is preferably greater than 0% by mass and not greater than 2.00% by mass, and more preferably 0.1% by mass to 1.50% by mass, from the viewpoint of preventing the cellulose ether from agglomerating.
[0026] The water content is defined as {(total mass of cellulose ether-absolute dry mass of cellulose ether) / (total mass of cellulose ether)}×100%.
[0027] Here, the term "total mass of cellulose ether" refers to the mass of cellulose ether accurately measured before drying according to the "loss on drying test" of the Japanese Pharmacopoeia (17th edition). The term "absolute dry mass of cellulose ether" refers to the mass of cellulose ether dried according to the "loss on drying test" of the Japanese Pharmacopoeia (17th edition).
[0028] The temperature of the acid aqueous solution to be contacted with the cellulose ether is 55° C. to 98° C., preferably 60° C. to 95° C., more preferably 63° C. to 90° C., and still more preferably 65° C. to 85° C. When the temperature of the acid aqueous solution is lower than 55° C., the amount of coarse aggregates and black contaminants generated increases. When the temperature of the acid aqueous solution exceeds 98° C., depolymerized cellulose ether having low yellowness cannot be obtained.
[0029] For example, a thermometer can be used to measure the temperature of the aqueous acid solution immediately before contacting the cellulose ether.
[0030] The method for heating the aqueous acid solution is not particularly limited. Examples of the method for heating the aqueous acid solution include a method in which the aqueous acid solution is placed in a container with a jacket and heated by hot water or steam in the jacket; and a method in which the aqueous acid solution is placed in a container with an electric heater and heated by energizing the electric heater.
[0031] Examples of methods for contacting cellulose ether at 45° C. to 95° C. with an aqueous acid solution at 55° C. to 98° C. include a method of adding the aqueous acid solution to cellulose ether stirred, for example, in a mixer; and a method of adding the cellulose ether to the aqueous acid solution stirred, for example, in a mixer. From the viewpoint of uniform contact between the cellulose ether and the aqueous acid solution, the method of adding the aqueous acid solution to the cellulose ether stirred, for example, in a mixer is preferred. In this method, from the viewpoint of uniform mixing of the cellulose ether to be depolymerized with the aqueous acid solution, the cellulose ether is preferably stirred at a rate of 1 rpm to 1000 rpm, and from the viewpoint of uniform mixing of the cellulose ether to be depolymerized with the aqueous acid solution, when the absolute dry mass of the cellulose ether to be depolymerized is regarded as 1 (i.e., 100%), the acid in the aqueous acid solution is preferably added at an addition rate of 0.01 mass% / min to 1.0 mass% / min.
[0032] Examples of the mixer include a reactor to be used for depolymerization of cellulose ether described later.
[0033] Examples of the aqueous solution of the acid to be used for depolymerization include aqueous hydrogen halides such as aqueous hydrogen chloride, aqueous hydrogen bromide and aqueous hydrogen iodide. Aqueous hydrogen chloride (hereinafter also referred to as "hydrochloric acid") is preferred from the viewpoint of easy removal of the acid after depolymerization.
[0034] The amount of the aqueous acid solution to be used can be calculated based on the acid concentration in the aqueous acid solution and the amount of the acid to be used.
[0035] From the viewpoint of controlling the viscosity of the depolymerized cellulose ether, the acid concentration in the aqueous acid solution is preferably more than 0% by mass and not more than 35% by mass, and more preferably 5% by mass to 20% by mass.
[0036] From the viewpoint of controlling the viscosity of the cellulose ether obtained by depolymerization, the amount of the acid to be used can be selected by multiplying the absolute dry mass of the pre-depolymerized cellulose ether by preferably 0.05% by mass to 3.00% by mass and more preferably 0.10% by mass to 1.50% by mass. The absolute dry mass of the cellulose ether can be determined by subtracting the mass of water contained in the cellulose ether from the mass of the cellulose ether. The water content of the cellulose ether can be determined according to the "loss on drying test" in the commonly used test of the Japanese Pharmacopoeia (17th edition).
[0037] Examples of the method of adding the aqueous acid solution include spraying, showering, and dripping the aqueous acid solution.
[0038] In particular, by depolymerizing the cellulose ether by contacting the cellulose ether at 45 to 95°C, preferably 60 to 90°C, more preferably 63 to 87°C, and even more preferably 65 to 85°C, with an aqueous acid solution at 55 to 98°C, preferably 60 to 95°C, more preferably 63 to 90°C, and even more preferably 65 to 85°C, the amount of coarse aggregates and black contaminants can be reduced.
[0039] During the addition of the acid aqueous solution, the cellulose ether is preferably kept at the temperature adjusted just before the addition of the acid aqueous solution. From the viewpoint of keeping the temperature of the cellulose ether at the same temperature before and after the contact with the acid aqueous solution, the cellulose ether to be contacted with the acid aqueous solution and the acid aqueous solution preferably have the same temperature, for example, 65° C. to 85° C.
[0040] From the viewpoint of allowing the cellulose ether after depolymerization to have low yellowness, the water content in the depolymerization reaction of the depolymerization step is preferably 1.0 mass% to 5.0 mass%, more preferably 1.5 mass% to 4.0 mass%. Here, the water content in the depolymerization reaction is the mass percentage of water in the total mass of the depolymerization reaction. When the water content in the depolymerization reaction is less than 1.0 mass%, depolymerized cellulose ether having low yellowness may not be obtained. When the water content exceeds 5 mass%, the amount of aggregates generated may increase.
[0041] When the cellulose ether and the aqueous acid solution are present separately at the start of the depolymerization reaction, the water content in the depolymerization reaction of the depolymerization step is represented by the ratio of the mass of water during the depolymerization reaction to the total mass of the aqueous acid solution and the cellulose ether. This can be represented as follows:
[0042] [{mass of water in the pre-depolymerized cellulose ether (kg) + mass of water in the acid aqueous solution (kg)} / {total mass of the pre-depolymerized cellulose ether and the acid aqueous solution (kg)}]×100.
[0043] The total mass (kg) of the pre-depolymerized cellulose ether and the acid aqueous solution is the sum of the mass (kg) of the pre-depolymerized cellulose ether and the mass (kg) of the acid aqueous solution. When optional components other than the cellulose ether and the acid aqueous solution are present at the start of the depolymerization reaction, the water content in the depolymerization reaction of the depolymerization step may be calculated taking into account the water content of the optional components and the total mass including the optional components. Examples of the optional components other than the cellulose ether and the acid aqueous solution include alcohols having two or less carbon atoms, such as methanol and ethanol.
[0044] The depolymerization step can be carried out, for example, in a reactor.
[0045] The reactor to be used for depolymerization of cellulose ether is not particularly limited. From the viewpoint of uniform depolymerization, the reactor is preferably a reactor capable of allowing cellulose ether particles to be uniformly stirred in the reactor, and examples thereof include a double cone type rotary reactor, an oblique cylindrical type rotary reactor, an internal stirring reactor, and a fluidized bed reactor. In addition, from the viewpoint of controlling the reaction temperature during depolymerization, the reactor to be used for depolymerization of cellulose ether is preferably equipped with a jacket. Two or more reactors may be used simultaneously in the depolymerization step.
[0046] The reaction temperature in the depolymerization step is substantially a temperature at which cellulose ether at 45 to 95° C. is contacted with an aqueous acid solution at 55 to 98° C. After the contact, an optional step of heating the obtained contact mixture to complete the depolymerization may be provided. From the viewpoint of controlling the viscosity of the depolymerized cellulose ether, the heating temperature is preferably 45 to 120° C., more preferably 60 to 100° C. When the cellulose ether is contacted with the aqueous acid solution, the respective temperatures of the cellulose ether and the aqueous acid solution may be different from the reaction temperature in the depolymerization step from the viewpoint of controlling the depolymerization reaction rate.
[0047] The depolymerization time in the depolymerization step is not particularly limited as long as the cellulose ether after depolymerization reaches a desired viscosity. From the viewpoint of obtaining a depolymerized cellulose ether having a low yellowness, the depolymerization time is preferably 0.1 to 4.0 hours, more preferably 0.1 to 2.0 hours. The depolymerization time refers to a period from the start of contacting the pre-depolymerized cellulose ether with an aqueous acid solution to the start of a degassing operation described below, or in the absence of a degassing operation, to the end of neutralization (by adding an alkali to the depolymerized cellulose ether-containing mixture obtained by depolymerization).
[0048] From the viewpoint of obtaining a depolymerized cellulose ether having a low yellowness, the addition time of the acid solution is preferably not more than half of the depolymerization time.
[0049] In order to reduce the residual amount of acid or salt generated by neutralization of the depolymerized cellulose ether after the depolymerization is completed, the pressure inside the system may be reduced (degassing) to remove the acid in the depolymerized cellulose ether. For example, when the aqueous acid solution is an aqueous hydrogen chloride solution, the method for producing the depolymerized cellulose ether may further include an optional step of removing hydrogen chloride under reduced pressure after the depolymerization step. From the perspective of efficient acid removal, the internal pressure of the reactor during degassing is preferably -60 kPaG to -98 kPaG.
[0050] An optional step of mixing the obtained depolymerized cellulose ether with a base to obtain a neutralized depolymerized cellulose ether may be performed. Examples of the base include weak bases such as sodium bicarbonate and sodium carbonate. The amount of the base added is not particularly limited as long as the acid is neutralized.
[0051] The neutralized depolymerized cellulose ether may be optionally comminuted and optionally sieved to pass through a sieve having a desired mesh size.
[0052] From the viewpoint of obtaining depolymerized cellulose ether having low yellowness, the viscosity reduction rate due to depolymerization in the depolymerization step is preferably 40.0 to 99.99%, more preferably 50.0 to 99.98%, and still more preferably 60.0 to 99.97%.
[0053] Here, the viscosity reduction rate after depolymerization refers to the ratio of the difference in viscosity of a 2 mass % aqueous solution of cellulose ether at 20° C. before and after depolymerization to the viscosity of a 2 mass % aqueous solution of cellulose ether at 20° C. before depolymerization. It can be defined as {(viscosity before depolymerization - viscosity after depolymerization) / viscosity before depolymerization}×100.
[0054] From the viewpoint of maintaining low viscosity of the coating liquid during film coating, the viscosity of a 2 mass % aqueous solution of the depolymerized cellulose ether at 20° C. is preferably 1.0 mPa·s to 20.0 mPa·s, more preferably 2.0 mPa·s to 20.0 mPa·s, and still more preferably 3.0 mPa·s to 15.0 mPa·s.
[0055] Example
[0056] Hereinafter, the present invention will be described in detail with reference to Examples and Comparative Examples. It should not be construed that the present invention is limited to or by the Examples.
[0057] The yellowness measurement, aggregate generation amount evaluation, and black contaminant generation amount evaluation were performed by the following methods.
[0058] <Measurement of yellowness>
[0059] A 2 mass % aqueous solution of the depolymerized cellulose ether was prepared, the temperature of the solution was 20° C., and the yellowness thereof was measured using an SM color computer (trade name “SM-4”, manufactured by Suga Test Instruments Co., Ltd.).
[0060] <Evaluation of the amount of aggregates generated>
[0061] 100 g of depolymerized cellulose ether was supplied to a sieve having a single-stage 4.7 mesh sieve (effective sieve area of 0.00314 m 2 After being screened by a Ro-Tap vibrating screen machine (produced by TAKEDA RIKAKOGYO Co., Ltd.) with an opening of 4.00 mm, the screen was screened at a rotation speed of 250 rpm and a vibration width of 50 mm for 1 minute without being impacted by a hammer. The amount of aggregates generated was evaluated by measuring the weight of the residue on the screen after screening.
[0062] <Evaluation of the amount of black contaminants generated>
[0063] 200 g of depolymerized cellulose ether was supplied to a sieve having a single-stage 18-mesh screen (effective screen area of 0.0314 m 2 After being sieved with a Ro-Tap sieve shaker (manufactured by TAKEDA RIKAKOGYO Co., Ltd.) with a sieve width of 0.85 mm and an opening of 0.85 mm, manufactured by Kansai Wire Netting Co., Ltd.), sieving was performed for 10 minutes at a rotation speed of 250 rpm, a vibration width of 50 mm and a hammer frequency of 67 times / min. Then, 2.5 g of the depolymerized cellulose ether obtained as the sieved portion was collected and uniformly distributed in a petri dish with a diameter of 10 cm, and the number of black contaminants with a size of 0.1 mm or more was visually counted. The above-mentioned collection of the depolymerized cellulose ether and the measurement of the amount of black contaminants were repeated 20 times, and the amount of black contaminants per 100 g (twice the total amount collected) was defined as the amount of black contaminants generated.
[0064] Example 1
[0065] 1.5 kg of HPMC (methoxy group content of 29.0 mass % and hydroxypropoxy group content of 9.1 mass %) was placed in a plow shear type internal stirring reactor with an internal volume of 10 L (PAM Apexmixer WB, produced by Pacific Machinery & Engineering Co., Ltd.), and stirred for 15 minutes at a main shaft speed of 150 rpm, a chopper speed of 1000 rpm and a jacket temperature of 60°C to adjust the temperature of HPMC to 50°C.
[0066] Next, 32.1 g of 14 mass % hydrochloric acid (0.30 mass % hydrogen chloride relative to the absolute dry mass of HPMC) adjusted to 73° C. in a hot water bath was added dropwise to the reactor over 30 seconds while continuously stirring the inside of the reactor, whereby the water content in the depolymerization reaction became 2.29 mass %. Then, stirring was continued for another 5 minutes after the addition. From the start to the end of the addition of 14 mass % hydrochloric acid, the temperature of HPMC was from 50° C. to 55° C.
[0067] Then, after the stirring was completed, 500 g of the mixture of HPMC and hydrochloric acid in the plow shears type internal stirring reactor was transferred to a 2L glass reactor (double cone type rotary reactor), and reacted in the glass reactor for 60 minutes while rotating the inside of the glass reactor, and the internal temperature of the glass reactor was maintained at 80° C. by heating the glass reactor in a water bath. Thereafter, the inside of the glass reactor was degassed under an internal pressure condition of −96 kPa to remove the hydrochloric acid, and then the remaining mixture was neutralized by adding sodium bicarbonate to obtain 500 g of depolymerized HPMC.
[0068] The depolymerized HPMC obtained was evaluated for the amount of aggregates generated and the number of black contaminants generated. Table 1 shows the properties of HPMC before depolymerization, the depolymerization conditions, and the properties and evaluation results of the depolymerized HPMC obtained.
[0069] Examples 2 to 8
[0070] Depolymerized HPMC was produced and evaluated in the same manner as in Example 1, except that the temperature of the pre-depolymerized cellulose ether and the temperature of the hydrochloric acid were changed to the temperatures in Table 1 by changing the jacket temperature and the hot water bath temperature. In Examples 2 to 3, the temperature of HPMC was from 60° C. to 65° C. from the start of adding 14% by mass of hydrochloric acid to the end. In Examples 4 to 8, the temperature of HPMC was from 67° C. to 75° C. from the start of adding 14% by mass of hydrochloric acid to the end. The results are shown in Table 1.
[0071] Example 9
[0072] Depolymerized HPMC was produced and evaluated in the same manner as in Example 1, except that the water content in the depolymerization reaction was changed to the water content in Table 1 by changing the hydrochloric acid concentration from 14% by mass to 8% by mass. The temperature of HPMC was from 60° C. to 65° C. from the start to the end of the addition of 8% by weight of hydrochloric acid.
[0073] Example 10
[0074] Depolymerized MC was prepared and evaluated in the same manner as in Example 1, except that HPMC was changed to MC (methoxy group content 29.4 mass %). The temperature of MC was from 70° C. to 75° C. from the beginning to the end of the addition of 14 wt % hydrochloric acid. The results are shown in Table 1.
[0075] Comparative Examples 1 to 3
[0076] Depolymerized HPMC was produced and evaluated in the same manner as in Example 1, except that the temperature of the pre-depolymerized cellulose ether and the temperature of the hydrochloric acid were changed to the temperatures in Table 1 by changing the jacket temperature and the hot water bath temperature. The results are shown in Table 1.
[0077] Comparative Example 4
[0078] Depolymerized HPMC was produced and evaluated in the same manner as in Example 9, except that the water content in the depolymerization reaction was changed to the water content in Table 1 by changing the hydrochloric acid concentration from 14 mass % to 8 mass %. The results are shown in Table 1.
[0079] Note that the depolymerized HPMC obtained in the examples and comparative examples was in the form of powder, and the color was uniform except for black contaminants. Therefore, it is believed that the depolymerization reaction was not locally performed but was performed uniformly.
[0080]
[0081] As is apparent from the results of Examples 1 to 9 and Comparative Examples 1 to 4, depolymerizing cellulose ether by contacting cellulose ether having a predetermined temperature with an aqueous acid solution having a predetermined temperature can produce depolymerized cellulose ether while reducing the amounts of generated aggregates and generated black contaminants and maintaining suppression of yellowness.
[0082] Furthermore, as is apparent from the results of Example 10, even if the type of cellulose ether is changed, the same effect can be achieved.
Claims
1. A method for producing depolymerized cellulose ether, the method comprising a depolymerization step of depolymerizing the cellulose ether, i.e., obtaining the depolymerized cellulose ether by contacting the cellulose ether at 45° C. to 95° C. with an aqueous solution of an acid at 55° C. to 98° C., The water content in the depolymerization reaction of the depolymerization step is 1.0 to 5.0 mass % based on the total mass of the materials of the depolymerization reaction, and the water in the depolymerization reaction is the sum of the water in the cellulose ether to be contacted with the aqueous acid solution and the water in the aqueous acid solution.
2. The method for producing depolymerized cellulose ether according to claim 1, wherein the temperature of the cellulose ether to be contacted with the aqueous acid solution, and the temperature of the aqueous acid solution are both in the range of 65°C to 85°C.
3. The method for producing a depolymerized cellulose ether according to claim 1 or 2, wherein the cellulose ether is selected from the group consisting of alkyl cellulose, hydroxyalkyl cellulose and hydroxyalkyl alkyl cellulose.
Citation Information
Patent Citations
Method for preparing very low viscosity cellulose ether and product
CN102807791A
Method of removing alkylene halogenohydrin from cellulose ether
CN103687652A